Education and Pandemic: Covid-19 and its effects on learning - Gaia, Everton Carlos Farias; Hingel, Silvio Augusto de Almeida; Ribeiro, Mílvio da Silva (Seven Editora, 2023)
The article relates to the COVID-19 pandemic and education, aiming to reflect on its implications for school learning in the pandemic context. It has interfered with the educational reality of students at all levels of education. Furthermore, it has also had an impact on the way modern society operates and lives since 2019. The concept of the COVID-19 pandemic and current educational thinking are developed in contrast to deficient educational systems, based on studies of the pandemic’s occurrence and educational practices during and after the peak of pandemic events. In this context, potential classifications, and typologies of educational systems in response to the pandemic reality are explored in a general sense. The conclusion is dedicated to evaluating the implications and challenges resulting from the COVID-19 pandemic, which has left significant marks on learning and the educational process in our educational institutions. DOI:https://doi.org/10.56238/sevened2023.004-014